2006
DOI: 10.1073/pnas.0510352103
|View full text |Cite
|
Sign up to set email alerts
|

Free radical production requires both inducible nitric oxide synthase and xanthine oxidase in LPS-treated skin

Abstract: Free radical formation has been investigated in diverse experimental models of LPS-induced inflammation. Here, using electron spin resonance (ESR) and the spin trap ␣-(4-pyridyl-1-oxide)-N-tertbutylnitrone, we have detected an ESR spectrum of ␣-(4-pyridyl-1-oxide)-N-tert-butylnitrone radical adducts in the lipid extract of mouse skin treated with LPS for 6 h. The ESR spectrum was consistent with the trapping of lipid-derived radical adducts. In addition, a secondary radical-trapping technique using dimethyl su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 43 publications
0
47
0
Order By: Relevance
“…GdCl 3 (10 mg/kg) was injected intravenously 24 h before the spin-trapping experiments [36]. Aminoguanidine (200 mg/kg) or 1400W (15 mg/kg) was administered 30 min or 1 h prior to spin trapping, respectively [37]. L-arginine (100 mg/kg) was administered 30 min prior to spin trapping.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…GdCl 3 (10 mg/kg) was injected intravenously 24 h before the spin-trapping experiments [36]. Aminoguanidine (200 mg/kg) or 1400W (15 mg/kg) was administered 30 min or 1 h prior to spin trapping, respectively [37]. L-arginine (100 mg/kg) was administered 30 min prior to spin trapping.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…15 The product of •OH reaction with DMSO has been demonstrated to be •CH 3 . 16 In addition, in xanthineluminal-xanthine oxidase assay, since alkaline DMSO can generate superoxide anion radicals, 17,18 DMSO as the solvent undoubtedly cause interference with the determination of superoxide radical scavenging.…”
mentioning
confidence: 99%
“…We and others have reported that nitrite can serve as a source of NO through XOR in models of vascular injury and pulmonary hypertension (23,24). XOR has been detected in skin, where it is involved in ROS production in response to lipopolysaccharide (LPS) (25) and ultraviolet irradiation (26). Thus, we hypothesize that XOR participates in normal wound healing through ROS/RNS and NO production.…”
Section: Xanthine Oxidoreductase Function Contributes To Normal Woundmentioning
confidence: 83%
“…We and others have shown that XOR is required for the beneficial actions of supplemental nitrite in the inhibition of intimal hyperplasia after vascular injury (23) and in reversing pulmonary hypertension (24). XOR expression in skin has been previously reported, linked to the pathogenesis of sunburn and skin inflammation (24,25). Beyond that, little is known about the role of XOR in the skin.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%